Peningkatan Karakter Empati Pada Sekolah Berbasis Budaya, SD Sanggar Anak Alam Nitiprayan Yogyakarta - Cindy Gupita Sari (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Today’s education tends to be conventional as it is merely indicated by transferring knowledge from teachers to students. In addition, a development on character is also often overlooked. The poor empathy between student and student as well as student and teacher must be very concerning. This study focuses on the achievement of students in acquiring knowledge, interpreting processes, evaluating, and making decision. The method in this study is qualitative. Data were collected using interview, observation, and documentation. Then, the three questions were asked, which were: 1) how do students acquire knowledge in meaningful learning? 2) how do students raise the empathy in everyday life? and 3) what are the roles of the facilitators in learning?. Based on the responses, three answers can be clustered, which were: 1) students gain knowledge from others and the surrounding environment provided the same opportunity to convey ideas by sitting together, 2) students learn to raise empathy through equal dialogue, and 3) the role of the facilitators is to encourage students to independently explore the surrounding environment and learn to respect others. Hence, this study is expected to aspire and to become a recommendation for formal schools in order to create a meaningful learning process and to raise empathy.